The challenges of measuring bleeding outcomes in clinical trials of platelet transfusions - Estcourt, L; Heddle, N; Kaufman, R; McCullough, J; Murphy, M; Slichter, S; Wood, E; Stanworth, S (Wiley, 2013)
Background: Many platelet (PLT) transfusion trials now use bleeding as a primary outcome; however, previous studies have shown a wide variation in the amount (5%‐70%) and type of bleeding documented. Differences in the way bleeding has been identified, recorded, and graded may account for some of this variability. This study's aim was to compare trials' method to document and grade bleeding. Study Design and Methods: Data were collected via three methods: a review of study publications, study case report forms, and a questionnaire sent to the authors. Authors of randomized controlled trials of PLT transfusion that used bleeding as an outcome measure were identified from the searches reported by two recent systematic reviews. Twenty‐four authors were contacted, and 13 agreed to participate. Data submitted were reviewed and summarized. Results: More recent studies with trained bleeding assessors, detailed documentation, and expanded grading systems have reported higher overall levels of bleeding. The World Health Organization grading system was widely used to grade bleeding, but there was no consistency in the bleeding grade definitions. For example, bleeding classified as Grade 2 in some studies (spreading petechiae) was classified as Grade 1 in other studies. Conclusions: This study has highlighted differences in the method of recording and grading bleeding, which may account for some of the variation in reported bleeding rates. To ensure that differences between studies can be attributed to trial interventions or types of participant included, this study group is developing consensus bleeding definitions, a standardized approach to record and grade bleeding, and guidance notes to educate and train bleeding assessors.